An immunomodulatory miniaturized 3D screening platform using liquefied capsules - Nadine, Sara (2022)
A critical determinant of successful clinical outcomes is the host's response to the biomaterial. Therefore, the prediction of the immunomodulatory bioperformance of biomedical devices following implantation is of utmost importance. Herein, liquefied capsules are proposed as immunomodulatory miniaturized 3D platforms for the high-content combinatorial screening of different polymers that could be used generically in scaffolds. Additionally, the confined and liquefied core of capsules affords a cell-mediated 3D assembly with bioinstructive microplatforms, allowing to study the potential synergistic effect that cells in tissue engineering therapies have on the immunological environment before implantation. As a proof-of-concept, three different polyelectrolytes, ranging in charge density and source, are used. Poly(L-lysine)-, alginate-, and chitosan-ending capsules with or without encapsulated mesenchymal stem/stromal cells (MSCs) are placed on top of a 2D culture of macrophages. Results show that chitosan-ending capsules, as well as the presence of MSCs, favor the balance of macrophage polarization toward a more regenerative profile, through the up-regulation of anti-inflammatory markers, and the release of pro-regenerative cytokines. Overall, the developed system enables the study of the immunomodulatory bioperformance of several polymers in a cost-effective and scalable fashion, while the paracrine signaling between encapsulated cells and the immunological environment can be simultaneously evaluated.